Off to class : incredible and unusual schools around the world - Hughes, Susan, 1960- (Owlkids, 2011)
When North American kids picture a school, odds are they see rows of desks, stacks of textbooks, and linoleum hallways. They probably don<U+2019>t picture caves, boats, or train platforms <U+2014> but there are schools in caves, and on boats and on train platforms. There<U+2019>s a whole world of unusual schools out there! But the most amazing thing about these schools isn<U+2019>t their location or what they look like. It<U+2019>s that they provide a place for students who face some of the toughest environmental and cultural challenges, and live some of the most unique lifestyles, to learn. Education is not readily available for kids everywhere, and many communities are strapped for the resources that would make it easier for kids to go to school. In short, it<U+2019>s not always easy getting kids off to class <U+2014> but people around the world are finding creative ways to do it.